2023
DOI: 10.23969/litigasi.v24i1.6208
|View full text |Cite
|
Sign up to set email alerts
|

Pengawasan Pelaksanaan Kesepakatan Mediasi Penal Dalam Penerapan Restorative Justice Pada Tahapan Penyidikan

Abstract: Restorative justice in the investigation is carried out by using the penal mediation method which provides an opportunity for the Victim and the Perpetrator in a participatory way to formulate a peace agreement facilitated by the Investigator. Penal mediation comes from civil mediation with problems in the process of drafting an agreement which must be ensured that it comes purely from the Parties. This research is a socio legal research conducted at the Directorate of General Criminal Investigation of the Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to police regulations, criminal cases that are unsuitable for Restorative Justice include state security issues, corruption, and crimes against human life. [21] Resolving criminal cases through Restorative Justice is typically conducted using penal mediation. "ganti rugi" within this mechanism is deeply intertwined with private dimensions, making penal mediation restitution-oriented.…”
Section: Challenges Of "Ganti Rugi" Within Diversion Restorative Just...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to police regulations, criminal cases that are unsuitable for Restorative Justice include state security issues, corruption, and crimes against human life. [21] Resolving criminal cases through Restorative Justice is typically conducted using penal mediation. "ganti rugi" within this mechanism is deeply intertwined with private dimensions, making penal mediation restitution-oriented.…”
Section: Challenges Of "Ganti Rugi" Within Diversion Restorative Just...mentioning
confidence: 99%
“…However, it should be noted that not all police jurisdictions adopt the same policy, as evidenced in several other studies which found instances of reconciliations not being resolved in immediate lump-sum payments. [21] This underscores the absence of a uniform mechanism guaranteeing the execution of "ganti rugi" in both diversion and Restorative Justice frameworks. Consequently, this results in disparate policies adopted by different institutions, perpetuating the potential risk of default in "ganti rugi" payments.…”
Section: Challenges Of "Ganti Rugi" Within Diversion Restorative Just...mentioning
confidence: 99%
“…If this happens to the losing party in court, then he or she will seek "justice" at a higher judicial level even up to the cassation level, causing cases to enter the courts to accelerate and cause a buildup of cases in the courts. [2] The settlement of criminal cases in restorative justice can bring together both parties to the case and involve both parties in reaching a mutually beneficial agreement so that the case does not have to go to court proceedings and a judge's decision that can cause resentment for the party sentenced by the judge. Restorative justice is basically a peaceful process that involves as far as possible those who have a role in a particular criminal offense and are collectively identified as suffering losses, and at the same time have needs and obligations with the intention of restoring them as much as possible and treating them as well as possible.…”
Section: Introductionmentioning
confidence: 99%